Deskripsi Kemampuan Sosial Terhadap Kedisiplinan Anak Usia Dini di TK Sayang Ibu Desa Girisa Kec Paguyaman Kab Boalemo - Tesya Iliya; Sri Wahyuningsi Laiya; Sulastya Ningsih (Inovasi Pendidikan dan Anak Usia Dini, 2025)
A Description of Sosial Skills and Discipline in Early Childhood at TK Sayang Ibu Kindergarten, Girisa Village, Paguyaman District, Boalemo Regency. Early Childhood Teacer Education, Faculty od Education, Universitas Negeri Gorontalo. Principal Supervisor: Sri Wahyuningsi Laiya S.Pd., M.Pd and Co-Supervisor: Sulastya Ningsih S.Pd., M.Pd. This study aims to describe children’s social skills, specifially their ability to interact effectively with others and their discipline, which can be observed through habitual behaviors and competencies in physical abilities, self-confidence, responsibility, discipline, social interaction, and emotional regulation. The rescarch employed a descriptive qualitative approach. The study involved 17 children, with the research subjects comprising the principal, educators, and parents. Data collection techniques included observation, interviews, and documentation. The findings revealed that the social skills related to discipline among 5-6 year-old children at Tk Sayang Ibu Kinderganten in girisa village had developed well. The chilren’s disciplinary attitudes demonstrated through daily routines, such as arriving on time and adhering to school schedules, indicated consistent and positive develoment.